2021
DOI: 10.48550/arxiv.2110.10174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hand-Object Contact Prediction via Motion-Based Pseudo-Labeling and Guided Progressive Label Correction

Abstract: Every hand-object interaction begins with contact. Despite predicting the contact state between hands and objects is useful in understanding hand-object interactions, prior methods on hand-object analysis have assumed that the interacting hands and objects are known, and were not studied in detail. In this study, we introduce a video-based method for predicting contact between a hand and an object. Specifically, given a video and a pair of hand and object tracks, we predict a binary contact state (contact or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Studies investigating the interactions revealed that key features of hand use included spatial and temporal information [44][45][46] and the common region involving a hand and a manipulated object [25,47]. Hand region alone was reported insufficient to detect a hand contact [48,49]. The application of these approaches to solve rehabilitation problems has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the interactions revealed that key features of hand use included spatial and temporal information [44][45][46] and the common region involving a hand and a manipulated object [25,47]. Hand region alone was reported insufficient to detect a hand contact [48,49]. The application of these approaches to solve rehabilitation problems has not been explored.…”
Section: Introductionmentioning
confidence: 99%